GEOSTATISTICS AND GIS IN THE DECISION MAKING OF THE USE OF INPUTS IN A PASTURE - Santos, K.E.L.; Bernardi, A.C.C.; Bettiol, G.M.; Crestana, S. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The present study aimed to apply the concepts of geostatistics and GIS to obtain management zones of a pasture Tanzania grass in São Carlos – SP/Brazil, and delimitation of management units for the application of liming and fertilization, based on the best interpolation method. Geostatistical analysis were performed based on results of soil analysis in order to evaluate the spatial dependence of the chemical attributes. The maps were obtained by Ordinary Kriging interpolation method and the definition of management zones was performed by fuzzy logic. From the maps of chemical parameters of the soil has resulted from the management zone map, resulting in five areas being: 0.02 ha (1.2% of total area) regarded as "very low" fertility; and 0.3 ha (18%) "low" fertility; 0.75 ha (44%) as "average" fertility; 0.55 ha (32%) as "high" fertility and, 0.08 ha (4.8%) as "very high" fertility. The comparison of the interpolation methods showed that Kriging Ordinary was the best methodology for the study. The geostatistics and gis have proved to be techniques that help with strategic and complex decisions in relation to the management of the agricultural production system.